Association between Polygenic Risk Score and One-Year Outcomes Following As-Needed Aflibercept Therapy for Exudative Age-Related Macular Degeneration - Taiyo Shijo; Yoichi Sakurada; Seigo Yoneyama; Wataru Kikushima; Atsushi Sugiyama; Mio Matsubara; Yoshiko Fukuda; Fumihiko Mabuchi; Kenji Kashiwagi (MDPI AG, 2020)
We investigated whether polygenic risk score (PRS) was associated with one-year outcome of as-needed aflibercept therapy for exudative age-related macular degeneration (AMD), including AMD (n = 129) and polypoidal choroidal vasculopathy (n = 132). A total of 261 patients were treated with as-needed intravitreal aflibercept injection (IAI) after three monthly IAIs and the completion of a one-year follow-up. One hundred and seventy-two healthy volunteers served as controls. Genotyping of ARMS2 A69S (rs10490924), CFH I62V (rs800292), SKIV2L-C2-CFB (rs429608), C3 (rs2241394), ADAMTS-9 (rs6795735) and CETP (rs3764261) was performed for all participants. A total of 63 PRSs were quantified. There was a positive association between the PRS involving ARMS2, CFH, C3, and ADAMTS-9 and best-corrected visual acuity at twelve months (p = 0.046, multiple regression analysis). When comparing PRSs of patients requiring retreatment and of patients without retreatment, 35 PRSs were significantly greater in patients requiring retreatment than in patients without requiring retreatment, with the PRS involving ARMS2 and CFH being most significantly associated (p = 1.6 × 10−4). The number of additional injections was significantly associated with 40 PRSs and the PRS involving ARMS2 and CFH showed a most significant p-value (p = 2.42 × 10−6). Constructing a PRS using a combination with high-risk variants might be informative for predicting the response to IAI for exudative AMD.